Firewood knowledge, use and selection by rural populations in the Dry Chaco of Sierra de Ancasti, Catamarca, Argentina - Jiménez-Escobar, N. David; Martínez, Gustavo J. (Ethnobiology and Conservation, 2018)
Firewood extraction and consumption are practices that require specific knowledge as well as detailed analysis of the cultural context in which they take place. The appropriation, use and selection of wood fuel resources were determined through open and semi-structured interviews, guided walks, participant observation and re-call. Currently, the rural inhabitants of the Sierra de Ancasti, Catamarca (Dry Chaco´s forest) know about, manage, use, and appropriate firewood resources to meet their needs related to heating and preparing food in their homes. We identified 52 species (corresponding to 44 genera, 23 families) associated with the domestic use of fire. Among these, 42 species (81%) are currently used for food preparation, 23 species (44%) in heating and 16 species (31%) in fire ignition and production. Based on an analysis of frequency of mention and the Cognitive Salience Index, the most important and preferred species among the inhabitants are Condaliaspp., Lithraea molleoides andVachellia caven. Factors that determine the selection of the species include firewood quality, accessibility and distance. Additional factors such as the high richness of firewood species used and known in the region, the flexibility of the inhabitants in their choice of species, the exclusive use of firewood for domestic purposes, collection of dead wood, and the use of several adventitious-cultivated species associated with domestic spaces, could be reducing the pressure on the native species and on the Dry Chaco forest in general.